2010
DOI: 10.1111/j.1460-9568.2010.07133.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and functional properties of distinct nicotinic acetylcholine receptors in the superior cervical ganglion of mice with targeted deletions of nAChR subunit genes

Abstract: Nicotinic acetylcholine receptors (nAChR) mediate fast synaptic transmission in ganglia of the autonomic nervous system. Here, we have determined the subunit composition of hetero-pentameric nAChRs in the mouse superior cervical ganglion (SCG), the function of distinct receptors (obtained by deletions of nAChR subunit genes), and mechanisms at the level of nAChRs that might compensate for the loss of subunits. As shown by immunoprecipitation and Western blots, wild type (WT) mice expressed (%): α3β4 (55), α3β4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(106 citation statements)
references
References 59 publications
8
96
2
Order By: Relevance
“…The similarity of the actions evoked by lidocaine in dissociated SCG neurons and in oocytes microtransplanted with muscle-type nAChR has two relevant implications: i) It indicates that lidocaine has similar modulating actions on different heteromeric nAChRs, including muscle-type and α3β4 nAChRs, which is the main subtype in sympathetic neurons; but also most likely over α3β4α5 and α3β4β2, which together constitute almost half the number of nAChRs in the mouse SCG neurons (David et al, 2010). This being of particular interest because many molecules acting on nAChRs have marked specificity on particular subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The similarity of the actions evoked by lidocaine in dissociated SCG neurons and in oocytes microtransplanted with muscle-type nAChR has two relevant implications: i) It indicates that lidocaine has similar modulating actions on different heteromeric nAChRs, including muscle-type and α3β4 nAChRs, which is the main subtype in sympathetic neurons; but also most likely over α3β4α5 and α3β4β2, which together constitute almost half the number of nAChRs in the mouse SCG neurons (David et al, 2010). This being of particular interest because many molecules acting on nAChRs have marked specificity on particular subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…In the peripheral and central nervous system there are different subtypes of nAChRs, generically called neuronal nAChRs. In mammalian autonomic ganglia neurons, including the superior cervical ganglion (SCG), the predominant nAChR is the heteromeric α3β4 subtype, though there are a significant percentage of combinations with α5 and/or β2 subunits (Gotti et al, 2009;David et al, 2010). Moreover, homomeric α7 receptors are also present, but their currents are only evoked in the presence of PNU 120569 (David et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunochemical and functional studies in rodents have shown that ganglionic neurons express high levels of α3β4 receptors in the somatic/dendritic compartment along with two minor populations of α3α5β4 and α3β2β4 receptors with different physiological and pharmacological properties (David et al, 2010;Mao et al, 2006). Low levels of α4* nAChRs may be expressed during development (Scholze et al, 2011).…”
Section: Nachrs In Autonomic Motoneuronsmentioning
confidence: 99%
“…Low levels of α4* nAChRs may be expressed during development (Scholze et al, 2011). α7 receptors are also expressed, although they are perisynaptic (Berg & Conroy, 2002) and their contribution to ganglionic transmission in rodents may be modest (David et al, 2010). nAChRs are also expressed on presynaptic terminals of ganglionic neurons where they positively regulate noradrenaline or acetylcholine release (Fischer, Orr-Urtreger, Role, & Huck, 2005;Kristufek, Stocker, Boehm, & Huck, 1999).…”
Section: Nachrs In Autonomic Motoneuronsmentioning
confidence: 99%